The role of self-determination in mediating between insan kamil-based religious internalization and the psychological happiness of santri-background students - Abdulloh Hadziq; Erika Setyanti Kusumaputri; Solmaz Bulut (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Despite extensive research on the influence of Islam on psychological happiness, few studies have explored specific Islamic theological constructs, such as insan kamil (perfect human). This study examines the relationships among the identification and introjection of Insan kamil-based religious internalization, self-determination, and psychological happiness, together with the mediating role of self-determination. Convenience sampling was used to identify 302 Santri-background Students in Special Region of Yogyakarta, Indonesia. The Insan kamil-based Religious internalization scale (identification and introjection dimensions) is an adaptation of the Christian Religious Internalization Scale, while the self-determination and psychological happiness scales were adopted from the Basic Psychological Need Satisfaction Scale and the Oxford Happiness Questionnaire. The data were analyzed using SEM based on PLS via Smart-PLS 3.0. The results show identification of insan kamil-based religious internalization positively relates to self-determination (β = .180, p = .013), but not directly to psychological happiness (β= .038, p = .325). The introjection of insan kamil-based religious internalization relates to self-determination (β= .249, p = .001) and psychological happiness (β= .255, p = .000). Furthermore, self-determination mediates the relationship between identification of insan kamil-based religious internalization and psychological happiness (β= .097, p =.014); and between introjection of insan kamil-based religious internalization and psychological happiness (β= .135, p = .001). The model explains 49% of the variance (R² = .49). Findings indicate that self-determination plays a vital role as a mediator. Pesantren (Islamic boarding schools) should integrate self-determination to enhance psychological happiness. This study also enriches Islamic psychology by connecting the happiness model with Islamic theology.